2006
DOI: 10.1159/000095044
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive CD30 Large Cell Lymphoma after Cyclosporine Given for Putative Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is not regarded as a predisposing condition for cutaneous T cell lymphoma. Cyclosporine (CsA) is an efficient therapy in AD, and its side effects, including lymphocytic proliferation, are rare at the low dose used in such cases. So far 3 cases of patients who developed cutaneous T cell lymphoma under CsA treatment for atopy have been described. An adult patient with a history of AD received CsA therapy because of an atypical flare-up of his eruption. He rapidly developed papular atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…CD30+ lymphoproliferative disorder in AD patients during cyclosporine therapy is rare and only four cases have been described [ Table 1]. [1][2][3][4] Cyclosporine is also used for psoriasis, which is accompanied by similar lymphoproliferative disorder. While some reports suggest no significant relation between AD and lymphoma, others suggest the positive correlation between cutaneous lymphoproliferative disorder and AD.…”
Section: Net Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…CD30+ lymphoproliferative disorder in AD patients during cyclosporine therapy is rare and only four cases have been described [ Table 1]. [1][2][3][4] Cyclosporine is also used for psoriasis, which is accompanied by similar lymphoproliferative disorder. While some reports suggest no significant relation between AD and lymphoma, others suggest the positive correlation between cutaneous lymphoproliferative disorder and AD.…”
Section: Net Lettermentioning
confidence: 99%
“…However, after using cyclosporine for AD, primary cutaneous CD30+ lymphoproliferative disorder (including lymphomatoid papulosis (LyP), primary cutaneous anaplastic large cell lymphoma (ALCL), and borderline lesion) is sporadically observed. [1][2][3][4] Recent report indicated that CD30+ T lymphocytes are up-regulated in the lesional skin of AD by mast cells which show the regulatory roles on both innate and acquired immunities. [5] A 57-years-old man was treated by topical corticosteroid ointment and antihistamine by a local dermatologist because of itchy chronic eruptions under a diagnosis of AD for about 20 years.…”
mentioning
confidence: 99%
“…Speculative, is it, in our case, a common stem cell/lymphoid precursor, having undergone one or more somatic events predisposing to cytokine-independent activation ofthe Jak3/Stat3 pathway, generated, through divergent differentiation, two distinct aberrant populations of T lymphocytes (i.e., CD8L GL and CD4'^ cells, respectively). Secondly, loss of immune competence resulting from long-standing CyA treatment may have favoured development and/or progression of MF in our case (4,11): cases have been reported where treatment with low-dose CyA (<5 mg/kg/day) following a misdiagnosis of inflammatory dermatoses led to clinical worsening and aggressive transformation of MF (16,17). Of note, in our patient the effect of continuous CyA administration may have been compounded by the relative immunosuppression which is known to be inherent in patients with lymphoproliferative conditions, including T-LGL disorders.…”
Section: Discussionmentioning
confidence: 84%
“…Most of them were CD30+ cutaneous lymphomas (6 cases), including lymphomatoid papulosis (2 cases) [9,10,11,12,13], but other types of CTCL have also been reported in association with AD: Sézary syndrome [14, 15] and mycosis fungoides [16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…Six of the 8 cases of CD30+ CTCL associated with severe longstanding AD occurred in the context of a ciclosporin treatment [9,10,11,12,13]. Concerns have recently been raised regarding a possible association between use of topical calcineurin inhibitors and cutaneous lymphoma [19].…”
Section: Discussionmentioning
confidence: 99%